Mastering Mac OS X v10.4 Tiger - Stauffer, Todd (Sybex, 2005)
This massive guide covers everything from the first moments after setting the hardware on the worktable to configuring and customizing web and FTP servers. Master practitioners Stauffer and McElhearn begin with the Mac OS X basics, including recent updates for this edition, the finder, using applications, personalizing, getting help and searching, dealing with PDFs, and working as the administrator. Their coverage on the Internet includes configuring access, security and managing email. Data on audio, video and personal information include working with iTunes and the iPod, working with digital images and video and managing contacts and appointments. They describe networking, connectivity and portables, including PowerBooks and iFiles, and they also cover hardware and maintenance such as fixing applications and managing Classic. Advanced topics include AppleScript and Automator, the command line and net security.